Clinical pharmacology of anti-hormonal drugs and gemcitabine in oncology: Bioanalysis - Therapeutic drug monitoring - Microdosing - van Nuland, Merel (Utrecht University, 2020)
The development of new drugs to treat cancer has increased significantly over the past years. Many of the newly developed targeted drugs are administered orally, causing an increased variability in drug levels and exposure compared to intravenously administered drugs. Variability in drug exposure may have consequences for treatment efficacy and toxicity. Therefore, a better understanding of the pharmacology - “the interaction between drugs and physiological processes” - may further optimize treatment and improve drug safety. In this thesis, the clinical pharmacology of anti-cancer drugs are described, with a focus on bioanalysis, therapeutic drug monitoring (TDM) and microdosing. Therapeutic drug monitoring, or TDM, is the clinical practice of measuring drug concentrations in biological matrix to be used for individualization of drug dosing, in other words patient-tailored dosing. TDM was shown to optimize treatment for abiraterone acetate, while there was no evidence found to support TDM of enzalutamide. Microdose trials are exploratory investigational drug trials in which 1/100th of the therapeutic dose, with a maximum of 100 μg, is administered to human subjects. The question raised is if microdose pharmacokinetics - “what the body does to a drug” - are indicative for pharmacokinetics at therapeutic dose. In a pilot study, we have shown that the volume of distribution and elimination pattern of gemcitabine differs after administration of microdose compared to a therapeutic dose.
Keywords: Bioanalysis; LC-MS/MS; TDM; microdosing; pharmacokinetics; abiraterone; enzalutamide; gemcitabine; SDG 3 - Good Health and Well-being